IJMA’ DALAM USHUL FIKIH (STISNU Aceh, 2022)
In Islamic legal theory (uṣul al-fiqh), ijmam is the third source of law after the Koran and sunnah (hadith). During the early legal schools of thought, the position of ijmaid was fourth. There was a shift in position after entering the Imam ash-Shafi'i period, and it was strengthened again in the classical period, the function and position of ijmaa became static, rigid, formal, final, not prospective for the future, and did not allow ijmaat to occur in the future. come. The concept of ijmaat during the early legal schools of law was a principle of justification to state the legitimacy of various different opinions, as an effort to find common ground and agree in establishing syar'i law. Al-Qur'an and sunnah are the propositions that create, while qiyas, ijmaak, and others are the propositions that reveal in finding the law. The concept of Ijmak was originally something dynamic and there was a harmonious integrative relationship between sunnah, ijtihad and ijmaak, but after the ash-Shafi'i period, ijmaq changed and shifted to be static, formal, not prospective for the future, the object of study is very limited, and Ijma is only possible during the friendship period, in the future it is not possible. It was even worse in the classical period, ijmaq became something that was final, and could not be changed until